Welfare Indicators in Tilapia: An Epidemiological Approach - Flores-García, Luis; Camargo-Castellanos, Juan C.; Pascual-Jímenez, Cristina; Almazán-Rueda, Pablo; Monroy-López, Jorge Francisco; Albertos-Alpuche, Pedro J.; Martínez-Yáñez, Rosario (Frontiers in Veterinary Science, 2022)
The interest and concern about the raising methods and their impact on animal welfare have increased. Production evaluation is population-based, and the welfare state analysis should be similar. In fish, the most common welfare indicators are gill state, fin damage, and body condition. The objective of this study was to evaluate the feeding rate effect on the welfare indicators of Oreochromis niloticus using an epidemiological approach. Five growth stages (from 1.2 to 360 g) were studied using four feeding rates as treatments, underfeeding (80%), recommended feeding (100%) and two overfeeding (120% and 140%). The evaluated welfare indicators include the presence of lesions in different body areas and fins, the decrease in body condition index, and their impact on biomass production. Incidence and relative risk were determined for each indicator. Statistically significant associations were found in the indicators of mortality, weight, body condition (K), and presence of evident damage in the caudal and anal fin in all stages. The results showed that the feed rate directly affects the welfare indicators and production. Mortality, weight reduction, K reduction, and caudal and anal fins damage incidence showed to be relevant indicators in all O. niloticus growing stages. As a result of this study, the epidemiological approach seems to be a valuable tool for production. A risk traffic light method is a proposal that could have great potential, with the suggested limits for WI’s concerning the individuals present in the culture pond, allowing progressive evaluation and decision-making to correct risky situations.